Reminders and Regrets - Chaudhry, Prof. M Lateef (Pakistan Journal of Ophthalmology, 2011)
Despite repeated editorials, communications, highlights, tips, pearls, lectures, seminars in the past I regret to say that still a considerable lot of ophthalmologists ignore the valuable recommendations of their learned colleagues in their clinical practice resulting in unsatisfactory at times catastrophic outcomes for their patients both in public and private setups.